Enhancing engineering ethics understanding: impact of the teaching and learning approaches and curriculum - Amir, Adibah; Ahmad, Zuraida; Toha @ Tohara, Siti Fauziah; Hasbullah, Nurul Fadzlin; Mel, Maizirwan; Haji Hassan, Masjuki; Ismail, Md Yusof (Kulliyyah of Engineering, 2023)
This study examines the understanding level of engineering students at Kulliyyah of Engineering (KOE), International Islamic University Malaysia (IIUM), Kuala Lumpur, in the course Engineering Ethics from Islamic Perspective, course code GENE 4300 that was designed to fulfil Engineering Accreditation Council (EAC) Program Outcomes (PO) No. 6,7 & 8 outlined by the Board of Engineers Malaysia (BEM). A survey was conducted among 135 respondents who enrolled in this course in semester 2 session 2022/2023, the survey assesses the impact of the course and identifies factors contributing to an increased understanding level of engineering ethics. The results showed, before taking the course GENE 4300, 19.27% of respondents said they have no understanding of engineering ethics, and after taking the course, it reduced to 0.75%. Similarly, before taking the course GENE 4300, none of the respondents opted for a very good understanding level in engineering ethics, after taking the course, 17.78% said their understanding level had increased to very good. Unanimously, all respondents agreed on the course’s importance and recommend its compulsory inclusion in the engineering curriculum. Notably, respondents attribute their enhanced understanding to the lecturers’ teaching abilities, despite 6 different lecturers are teaching this course in 6 different sections for this particular semester. It is an interesting finding of this study that highlights the strength of this course is the success of the curriculum in preparing engineering students for ethical challenges in the industry, regardless of multiple lecturers delivering the course. This study emphasizes the need for mandatory implementation to cultivate professional ethical engineers upholding the BEM code of ethics.